Identification of An Antigenic and Potential Diagnostic Marker of Leishmania donovani Infection by Immunoblot Assay - Manandhar, Krishna D (Nepal Journal of Science and Technology, 2013)
Leishmania donovani parasites from a sodium antimony gluconate (SAG) refractory patients of endemic region were cultured for extraction of crude soluble antigen and performed Western blot with sera from 138 subjects of different groups for diagnosis of Kala azar. The pretreated patients, however, frequently showed 18 bands of different molecular weight, the 85, 74, 63, 31, and 28 kDa were the major proteins against which more than 75% patients developed antibodies. The 74 kDa protein fraction band, which was consistently present in all the pretreated patients(n=35), completely waned out or found in state of virtually absent gloomy band in the six-month follow up patients (n=24). Furthermore, the band was absent in 91% of healthy controls from endemic population(n=33) and was absolutely absent in non-endemic(n=13) and other diseased(n=19) subjects. Although the band was present in 86% of Day 31 subjects(n=14), the average integrated density value (5110±634) of the paired samples was significantly less (p value, <0.0001) than that of Day 0 (11385±1230). The nature of the antigen showed its diagnostic and prognostic importance along with marker for kinetic recovery. Sensitivity and specificity of the protein were absolute in patients and non-endemic population, however, sensitivity was 94% in endemic population. Moreover, it did not show cross-reactivity to different disease groups. Hence, it could be a good diagnostic tool for Kala-azar disease.] Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 63-72 DOI: http://dx.doi.org/10.3126/njst.v13i2.7716